Moderating role of rational thought process in measuring the relationship between emotional attachment and branch trust - Kiran Mahmood; Mutahir Hussain; Farman Afzal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The objective of the study is to explore the moderating effect of rational thought process to measuring the relationship between emotional attachment and brand trust. The theoretical model has been drawn and tested by using hierarchal multiple regression model. To get more appropriate results, a CASC scale instrument that was developed by (Buck et al. 2004) that consist of rational thoughts and emotions has been adopted. The data was collected from the sample of 296 participants representing the main users including students and job holders of Pakistan who consumed carbonated drinks in their routine life. Statistical software SPSS version 16.0 employed for factor analysis, correlation and regression analysis. The significant and positive result shows that emotional attachment has a directly or indirectly impact on brand trust through the moderation effect of rational thoughts. This study provides firms to create emotional advertisements according to the rational behavior of consumers and develop different strategies to make strong brand trust of products in the mind of consumers.
Keywords: 330; emotional attachment; brand trust; rational thoughts